Assessment of Bedugul Geothermal Prospect Using A Numerical Reservoir Modeling - Renaldio Jackli Keintjem; Heru Berian Pratama; Adrian Tawakal; Andrian Putra Wardana; Muhamad Ridwan Hamdani; Yuniar Zhafira Abdillah; Sutopo Sutopo (Indonesian Journal on Geoscience, 2023)
A numerical modeling was carried out to generate a numerical model of the Bedugul geothermal field located in Bali Island, Indonesia. This study presents a natural state model and updates the conceptual model of Bedugul based on published geological, geophysical, geochemical, and well data. The numerical simulation of the Bedugul geothermal field has been developed using the previous conceptual model and well data. The Bedugul reservoir model is properly aligned with actual Pressure and Temperature well data. Thus, the natural state model is used to update the Bedugul conceptual model. The main updated points of the conceptual model were the location of the heat source to be beneath Mount Tapak, adding the flow fluid pattern as outflow and upflow location, caprock, reservoir, recharge, discharge, and adding iso-temperature distribution. Based on the numerical model result, the Bedugul geothermal field is a waterdominated geothermal system. The results of this model have been applied to the heat stored method with the Monte Carlo simulation to generate a probabilistic distribution of the reserve potential estimation. The probabilistic for P50 of probable and proven reserve estimation for thirty years are 136.3 MW and 33.4 MW, respectively. Keywords: Bedugul, numerical model, natural state, resource assessment, geothermal